Odyssey Self Reflection - knitting yarns / Faculty of Art and Design UiTM Cawangan Sarawak - Mohd Rathi, Mohd Razif (Perpustakaan Tun Abdul Razak, PTAR Universiti Teknologi Mara Cawangan Sarawak, 2021)
My artwork is about my childhood memories with my mother. The principle in the artworks were repetition, highlighting the form of knitted flower and knitting yarn. I used the knitting technique for my sculpture. I used mixed media for my drawing which is soft pastel, charcoal on paper. Meanwhile for the painting, I used acrylic colours to colour the subject and used etching technique for printmaking.